Farm workers in Stellenbosch: A survey of factors affecting health - Abie_ZH-B (Department of Public Health and Family Medicine, 2024)
This is a cross-sectional study describing the condition of farm workers in the Stellenbosch area of South Africa. The study was done to establish a profile of farm workers' health; and to investigate the extent to which the health of farm workers may be impaired by identified factors, both environmental and non-environmental. Objectives: To describe the conditions of life of farm workers and families To describe harmful exposures on farms and their effects on the health of farm workers and their families To evaluate the access of farm workers and their families to health services Methods: The study design was a cross sectional analytic survey, undertaken in the latter half of 1998, using all Stellenbosch farms as the sampling frame, of which 90 were selected by random procedure. The farms were surveyed in two stages. The first stage was a household survey, followed a few days later by an individual survey. The household survey enumerated all individuals on the farm in house-to-house interviewing of a responsible adult from each household. Using information from the household survey, the individual survey sampled all children under 9 years, all adults aged 55 years or more, and every 5th adult in the age range 15 - 54 years. Eight trained interviewers used 6 a standardised household questionnaire, and separate questionnaires for each of the individual interviews. Findings: the main findings of the study were the fact that the conditions of work and life for farm workers were poor. We found that the illegal DOP system is still in practice on 8% of the farms where the literacy rate amongst the community was also found to be very low. This had lead to the unavoidable heavy drinking habits. Only 4% of the population attended school to learn to read and write in a community where overcrowding (24% of the population) and low wages for workers (20% of the workers earn less than R 900) were already posing a threat to healthy lifestyles and indicating poor living conditions. One of the direct consequences of these being teenage pregnancy (age at first pregnant could be as low as 12 years of age) and trauma requiring the attention of a health care worker, which 7% of the participants had experienced only a month before the survey. Apart from disability which 28% of participants said was a direct consequence of a trauma, this study also found that farm workers were faced with medical conditions such as hypertension, headache etc